The Analysis of Region Potential for Ruminant Development in Polewali Mandar District, West Sulawesi Province, Indonesia - Indah, Andi Sukma; Hajar, Hajar (Jurnal Peternakan, 2025)
ABSTRACT.  This study aims to identify the potential of Polewali Mandar Regency as a ruminant development area based on the analysis of regional potential and forage availability. Identify the condition of the Polewali Mandar Regency area regarding the availability of forage and analyze the feasibility of the area for the development of ruminant farming. The method used to carry out the analysis was the analysis of livestock density and LQ, and the analysis of the carrying capacity of forage and agricultural waste to develop ruminants in the Polewali Mandar Regency. The data used in the analysis is secondary data from the Agriculture and Livestock Service Office of Polewali Mandar Regency and the Central Bureau of Statistics of Polewali Mandar Regency. The data analysis method used is descriptive-analytical. Recommendations for livestock types to be developed based on the LQ analysis results are cattle-based in Tubbi Taramanu, Wonomulyo, Mapilli, Bulo and Matangnga sub-districts, buffalo-based in Tinambung and Campalagian sub-districts, and goat base in Balanipa, Limboro, Alu, Campalagian, Luyo, Tapango, Matakali, Polewali, Binuang, and Anreapi sub-districts. CCI analysis shows that only the Tapango, Wonomulyo, and Binuang sub-districts are in a safe status. The RDP analysis shows that most sub-districts in Polewali Mandar can increase their livestock population, with the Tapango sub-district having the highest population increase capacity. The recommendation results are a preliminary analysis of ruminant development, so further studies are needed.